Imperforata Hymen: Secondary Urinary Retention due to Hematocolpos Compression in a 13-Year-Old Woman - Sentosa, I Gede Bagus; Kurniawan, Rommy Andika (Fakultas Kedokteran Universitas Brawijaya, 2024)
Imperforate hymen is a rare congenital anomaly in which the hymen completely covers the vaginal opening, caused by the failure of vaginal plate canalization during the embryonic period. This article reported a 13-year-old girl with a chief complaint of cyclic monthly lower abdominal pain, suprapubic pain, and inability to urinate. She denied prior menstruation. Cystic mass was palpated in the suprapubic area, and the hymen was seen covering the entire vaginal introitus. Hematometra and hematocolpos were found on abdominal ultrasonography and the patient was diagnosed with imperforate hymen. Hymenectomy was performed and she had regular menstruation afterwards. If left untreated, it can lead to morbidities such as infection, endometriosis, subfertility, and kidney failure. It is essential for clinicians to consider imperforate hymen as the differential diagnosis and examine the external genitalia, especially in adolescents with cyclic monthly lower abdominal pain and amenorrhea.